Meta-Analysis of Higher PEEP Strategies' Effects on Mortality Rates and Inflammatory Mediators in Patients with ARDS: A Perspective Review on Patients with Severe COVID-19-Associated ARDS - Supranoto, Yehuda Tri Nugroho; Negara, I Made Putra Wira (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background: Different strategies of positive end-expiratory pressure (PEEP) in mechanical ventilation are crucial for patients with coronavirus disease 2019 (COVID-19)-associated acute respiratory distress syndrome (ARDS). PEEP acts as a “double-edged sword” for ARDS patients. PEEP could recover pulmonary atelectasis but can induce alveolar hyperinflation.Objective: This review aimed to evaluate the effect of higher PEEP in patients with severe COVID-19-associated ARDS.Method: This meta-analysis included randomized controlled trial (RCT) studies to assess the mortality rates, barotrauma events, and inflammatory mediators modulation due to higher PEEP strategies. The pooled effect of the mortality rates and barotrauma events were presented as risk ratios (RR) with 95% confidence of interval (CI) using random-effects model (REM) or fixed-effects model (FEM).Results: We identified twelve RCTs comparing higher versus lower PEEP in ARDS patients. There was unsignificant result in overall mortality rates group [RR=0.94,95%CI(85,1.03),p=0.21] but not in mortality after positive response of oxygenation group [RR=0.88,95%CI(0.81,0.95),p=0.002] in higher PEEP group. In terms of patients without positive response of oxygenation, higher PEEP group had significantly higher mortality rates [RR=1.07,95%CI(1.00,1.15),p=0.06]. Higher PEEP significantly reduced the mortality rates in ARDS patients with PaO2/FiO2<150 mmHg [RR=0.867,95%CI(0.74,1.00),p=0.04] instead of patients with moderate ARDS (PaO2/FiO2 ≥150 mmHg) [RR=1.12, 95%CI(0.85,1.47), p=0.44]. There were no differences in overall barotrauma events [RR=1.03,95%CI(0.78,1.36),p=0.85] between higher and lower PEEP group. The use of higher and lower PEEP also contribute to the modulation of inflammatory mediators including TNF-α, IL-6, IL-1RA, and IL-8.Conclusion: Higher PEEP could reduce the mortality of patients with ARDS who responded to the oxygenation. Higher PEEP does not increase the risk of overall barotrauma events. Higher PEEP can modulate the inflammatory mediators.